Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A=-4/7.2/9+-4/7.7/9+18/7
= -4/7.(2/9+7/9)+18/7
= -4/7.1+18/7=-4/7+18/7=14/7=2
A= -4/7. 2/9+ -4/7.7/9 + 18/7
A =-4/7.(2/9+7/9)+18/7
A =4/7.1+18/7
A=4/7+18/7
A=22/7
\(\frac{9}{27}=-\frac{5}{a}\)
=>-5x27=a x 9
a=-5x27/9
a=-15
-5/15=b/-18
=>-18x5/15=b
b=-6
Ta có:
=
=\(\left(1+1+...+1\right)-\)\(\left(\frac{1}{10}+\frac{1}{40}+\frac{1}{80}+...+\frac{1}{1120}\right)\)
=11\(-\left[\left(\frac{1}{2}-\frac{1}{5}+\frac{1}{5}-...\frac{1}{35}\right).\frac{1}{3}\right]\)
=11\(-\left[\left(\frac{1}{2}-\frac{1}{35}\right).\frac{1}{3}\right]\)
=11\(-\left(\frac{33}{10}.\frac{1}{3}\right)\)
=11\(-\frac{11}{70}\)
\(\frac{4}{3}B=-1+\frac{3}{4}-\left(\frac{3}{4}\right)^2+...+\left(\frac{3}{4}\right)^{99}\)
\(B=-\frac{3}{4}+\left(\frac{3}{4}\right)^2-\left(\frac{3}{4}\right)^3+...+\left(\frac{3}{4}\right)^{100}\)
\(\Rightarrow\)\(\frac{7}{3}B=-1+\left(\frac{3}{4}\right)^{100}\Rightarrow B=\frac{\left(\frac{3}{4}\right)^{100}-1}{\frac{7}{3}}=\frac{3\left[\left(\frac{3}{4}\right)^{100}-1\right]}{7}\)
Như vầy đủ gọn chưa bạn?
=Xx10-(10+9+8+...+2+1) =20-15
=Xx10-(10+9+8+...+2+1) =5
Xx10-55 =5
Xx10=55+5
Xx10=60
X =60:10
X=6
(x-1) + (x-2)+(x-3)+ ....+(x-9)+(x-10) = -20-15
(x+x+x+...+x) - (1+2+3+4+...+9+10) = -35
=> 10x -55 = -35
=> 10x = -35 +55
=>> 10x = 20
=> x = 20 : 10
=> x = 2
\(\left(2^3.9^8.5\right):\left(9^2.\left(10-1\right)\right)\)
\(=2^3.9^8.5:9^3\)
\(=2^3.9^5.5\)
\(\left(2^3.9^4.9^3.45\right):\left(9^2.10-9^2\right)\)
(=) \(\left(2^3.3^8.3^6.5.3^2\right):9^2\left(10-1\right)\)
(=) \(\left(2^3.3^{15}.5\right):3^4.3^2\)
(=) \(2^3.3^9.5\)
110 - 9 = 101
=101.hêhêhê